Cybersecurity and Evolutionary Data Engineering Select Proceedings of the 2nd International Conference, ICCEDE 2022 - Jain, Raj.; Travieso, Carlos M.; Kumar, Sanjeev (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book comprises the select proceedings of the 2nd International Conference on Cybersecurity and Evolutionary Data Engineering (ICCEDE 2022). The contents highlight cybersecurity and digital forensics, evolutionary data engineering, and data management for secure contemporary applications. It includes papers on data models, semantics, query language; AI-driven industrial automation, ERP, CRM data security; authentication and access control; cyberspace structure and models; and drone large data filtration, cleansing, and security, among others. This book is of immense interest to researchers in academia and industry working in the fields of electronics and data engineering.
Current Status of Challenges in Data Security: A Review -- Cyber Bullying: The growing menace in cyber space with its challenges and solutions -- Hybrid Feature Extraction for Analysis of Network System Security - IDS -- Stranger Trust Architecture: An advancement to Zero Trust Architecture -- Genetic algorithm optimized SVM for DoS Attack Detection in VANETs -- Digital and IoT forensic: Recent trends, methods and challenges -- Cloud Based Occlusion Aware Intrusion Detection System -- Comparative Analysis of Web Application based Encryption Methods -- Linking of Ontologies for Composition of Semantic Web Services using Knowledge Graph -- Fake image dataset generation of Sign Language using GAN -- Analysis of Multimodal Biometric System based on ECG Biometrics -- Performance Analysis of Nature Inspired Optimization based Watermarking Schemes.
Keywords: Data protection; Engineering -- Data processing; Cooperating objects (Computer systems).; Data and Information Security; Data Engineering; Cyber-Physical Systems